Method for detecting and recovering copper ions by using carbon dots

By using carbon dots for quantitative fluorescence detection and flocculation recovery, the high cost and low efficiency of removing II valence copper ions in wastewater in the prior art is solved, and efficient and environmentally friendly copper ions recovery is achieved.

CN119555653APending Publication Date: 2025-03-04KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411929748.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, low efficiency, possible secondary pollution and difficulty in effectively recovering heavy metal ions when removing II valence copper ions in wastewater.

Method used

Carbon dots are used to detect the II valence silver ions in quantitative fluorescence, and the precise recovery of II valence copper ions is achieved by forming stable complexes and flocculation.

Benefits of technology

It realizes accurate detection and efficient recycling of II-valent copper ions, reduces treatment costs, reduces environmental pollution, and has good application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209985640000071
    Figure BDA0005209985640000071
  • Figure HDA0005209985650000011
    Figure HDA0005209985650000011
  • Figure HDA0005209985650000012
    Figure HDA0005209985650000012
Patent Text Reader

Abstract

The invention relates to the field of environmental engineering and waste recycling, in particular to a method for detecting and recycling copper ions through carbon dots, amines and acids are used as precursors, the carbon dots with fluorescence are prepared through a microwave-assisted thermal method, the prepared carbon dots are used for quantitative fluorescence sensing and flocculation recycling of II-valent copper ions, and the method for detecting and recycling the copper ions through the carbon dots is suitable for industrial production. The higher the concentration of the II-valent copper ions is, the lower the fluorescence intensity is, a standard linear relation exists between the two, in addition, the obtained carbon dots can also be combined with the II-valent copper ions to form a complex to generate flocculation and calcination to obtain copper oxide, and the II-valent copper ions in the waste are recycled; the preparation method of the carbon dots is simple and efficient, large-scale batch preparation can be achieved, the carbon dots can achieve accurate detection of the II-valent copper ions, the detection limit is extremely low, accurate separation and extraction of the II-valent copper ions can be achieved, the recovery efficiency is high, the cost is low, and practicability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of environmental engineering and waste recycling, and in particular to a method for accurately detecting and accurately recovering copper ions using carbon dots. Background Art

[0002] Water pollution is one of the major environmental issues facing the world today, especially heavy metal pollution. Copper ions are one of the common industrial wastewater pollutants, widely derived from industrial processes such as metallurgy, electronics, printing, electroplating, and fertilizers. Copper II ions are toxic to aquatic organisms when present in high concentrations and pose a serious threat to human health. Therefore, it is urgent to develop efficient, environmentally friendly and economical water treatment technologies.

[0003] At present, common methods for removing II-valent copper ions from wastewater include the following: chemical precipitation, ion exchange, membrane separation (such as reverse osmosis), and adsorption. However, they generally have the following problems: high cost and low efficiency: For example, ion exchange and membrane separation are not only expensive in equipment, but also have low recovery efficiency, making them difficult to adapt to large-scale applications. Secondary pollution: Traditional chemical precipitation and adsorption methods may produce waste residues or waste liquids, increasing the risk of environmental pollution. Difficulty in recovery: Most current methods for removing II-valent copper ions are difficult to effectively recover heavy metal ions or treatment materials after treatment, which makes it difficult to fully utilize resources. Therefore, there is an urgent need for a new method that can simultaneously achieve efficient removal of II-valent copper ions and recover II-valent copper ions after treatment, thereby reducing treatment costs and reducing environmental pollution.

[0004] Carbon dots (CDs) are a class of carbon-based materials with nanoscale size, good water solubility and tunable optical properties. Due to their unique structure and properties, carbon dots have a wide range of applications in optoelectronics, bioimaging, sensors and water treatment. Compared with traditional adsorption materials, carbon dots have the following advantages: Non-toxicity and biocompatibility: carbon dots are safer than other metal or synthetic materials. Good water solubility and high surface area: the surface of carbon dots contains rich functional groups, which can effectively interact with heavy metal ions in water. Optical properties: the tunable fluorescence properties of carbon dots make it possible to detect heavy metal ions with high sensitivity. Summary of the invention

[0005] In order to achieve the above objectives, the present invention proposes a method for accurately detecting and accurately recovering II-valent copper ions using carbon dots, which can not only realize fluorescent quantitative detection of II-valent copper ions, but also form stable complexes with II-valent copper ions and produce flocculation. The carbon dots can be removed by calcination and flocculation to achieve the recovery of II-valent copper ions, and has great potential application value.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0007] A method for detecting copper ions using carbon dots, the specific steps are as follows:

[0008] (1) adding carbon dots to solutions containing different concentrations of II-valent copper ions to obtain dispersions of different concentrations of II-valent copper ions, dispersing the carbon dots into solutions of the same volume to obtain blank carbon dot solutions, wherein the concentrations of the carbon dots in the two solutions are both 1 to 100 μg / mL;

[0009] (2) Using a fluorescence spectrometer to measure the fluorescence intensity F1 of the dispersion and the fluorescence intensity F0 of the blank carbon dot solution;

[0010] (3) Fit the fluorescence intensity F1, the fluorescence intensity F0 and the concentration of II-valent copper ions in the dispersion to obtain the logarithm of the fluorescence intensity F1 10 The linear relationship curve between F1 and II-valent copper ion concentration was obtained to obtain a linear fitting equation. The II-valent copper ion concentration in the solution was calculated according to the fluorescence intensity of the solution, and the copper ions in the solution were quantitatively detected.

[0011] The preparation method of step (1) carbon dots is as follows: dissolving an organic amine and an organic acid in pure water, ultrasonically dispersing to prepare a precursor solution, adding an inorganic acid to adjust the pH value of the precursor solution to 1-7, heating the solution with a microwave until a solid product is obtained, adding ultrapure water to the solid product for ultrasonic dispersion, filtering with a microporous filter membrane to obtain a filtrate, dialyzing the filtrate, and freeze-drying the dialyzed solution to obtain carbon dot powder.

[0012] The organic amines are fatty amines (methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, etc.), alcoholamines (monoethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, etc.), amides (formamide, acetamide, propionamide, butyramide, isobutyramide, acrylamide, polyacrylamide, caprolactam, dimethylformamide (DMF), dimethylacetamide (DMAC), etc.), alicyclic amines (triethylene glycol, diethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, etc.), The organic acids include aliphatic organic acids (monocarboxylic acids, dicarboxylic acids and polycarboxylic acids), aromatic organic acids (benzoic acid, salicylic acid, caffeic acid, chlorogenic acid, quinic acid, gentisic acid, protocatechuic acid, phthalic acid, vanillic acid, p-coumaric acid, etc.), and the like.

[0013] The molar ratio of the organic amine to the organic acid is 1:5 to 5:1, and the volume of pure water is 5 to 100 times the total volume of the organic amine and the organic acid.

[0014] The inorganic acid is hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc.; the microwave power is 50-1000W, and the microwave reaction time is 0.5-20min.

[0015] The pore size of the microporous filter membrane is 0.10-0.45 μm; the molecular weight cutoff of the dialysis bag is 500-1500 Da.

[0016] The fluorescence intensity of the present invention is measured by an F97Pro fluorescence spectrometer.

[0017] The present invention also provides a method for recovering II-valent copper ions using carbon dots, the specific steps of which are as follows:

[0018] (a) continuously adding carbon dots to a II-valent copper ion solution until no flocculation occurs, thereby obtaining a suspension;

[0019] (b) centrifuging the suspension, collecting the flocculated precipitate, washing the flocculated precipitate with ultrapure water, and then drying;

[0020] (c) calcining the dried product in air to obtain copper oxide, which is then washed, dried, collected, weighed, and stored.

[0021] In step (b), the centrifugal speed is 5000-10000 r / min, and the centrifugal time is 5-10 min.

[0022] In step (c), the calcination temperature is 500-1000° C., the calcination time is 0.5-3.0 h, and the calcination atmosphere is air.

[0023] Beneficial effects of the present invention:

[0024] (1) The carbon dot preparation method proposed in the present invention is simple and efficient and can be prepared on a large scale.

[0025] (2) The carbon dots prepared by the present invention can achieve accurate detection and quantification of II-valent copper ions with an extremely low detection limit.

[0026] (3) The carbon dots prepared by the present invention can realize the precise separation and extraction of II-valent copper ions with high recovery efficiency, low cost and strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the emission spectra of the carbon dots prepared in Example 1 at different excitation wavelengths;

[0028] Figure 2 TEM image of the carbon dots prepared in Example 1;

[0029] Figure 3 is the XRD pattern of the carbon dots prepared in Example 1;

[0030] Figure 4 The emission spectra of the fluorescent carbon dots after adding different concentrations of II-valent copper ions in Example 6;

[0031] Figure 5 The fitting curve of the logarithm of the fluorescence intensity F1 and the concentration of the II-valent copper ion after adding different concentrations of II-valent copper ions in Example 6;

[0032] Figure 6 The emission spectra of the fluorescent carbon dots after adding different concentrations of II-valent copper ions in Example 7;

[0033] Figure 7 The fitting curve of the logarithm of the fluorescence intensity F1 and the concentration of the II-valent copper ion after adding different concentrations of II-valent copper ions in Example 7;

[0034] Figure 8 This is a photo of the flocculation precipitation taken in Example 8;

[0035] Fig. 9 The SEM and element distribution diagram of the flocculation precipitation in Example 8;

[0036] Fig.10 The SEM and element distribution diagram of the product obtained by flocculation precipitation and calcination in Example 8;

[0037] Fig.11 This is the XRD pattern of the calcined sample in Example 8. DETAILED DESCRIPTION

[0038] The following is a specific implementation of the present invention, and the examples and drawings are for further describing the present invention. The following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0039] Example 1

[0040] The preparation method of carbon dots is as follows:

[0041] 0.86 g of o-phenylenediamine and 0.6 g of tartaric acid (molar ratio = 1:1) were weighed and dispersed in a conical flask filled with 40 mL of ultrapure water. The precursor solution was prepared by ultrasonic dispersion for 20 minutes. The pH of the precursor solution was adjusted to 1.0 by adding 1 mol / L hydrochloric acid, and then microwaved at a power of 700 W for 6 minutes to obtain a solid product. During purification, ultrapure water was added for ultrasonic dispersion, and the product was filtered through a 0.10 μm filter membrane for 3 times to obtain a filtrate. The filtrate was then dialyzed for 24 hours using a dialysis bag with a molecular weight cutoff of 500 Da. Finally, the dialyzate was freeze-dried to obtain carbon dot powder, recorded as B-CDs.

[0042] Figure 1 1 is the emission spectra of the carbon dots prepared in Example 1 at different excitation wavelengths, indicating that B-CDs are not excitation-dependent and have the strongest fluorescence emission under 325 nm excitation.

[0043] Figure 2 This is the TEM image of the carbon dots prepared in Example 1. It can be seen that the B-CDs are nearly spherical and evenly dispersed, and the average size of the B-CDs is 3.01 nm.

[0044] Figure 3 The XRD pattern of the carbon dots prepared in Example 1 shows the microcrystalline nature of the carbon dots.

[0045] Example 2

[0046] The preparation method of carbon dots is as follows:

[0047] 0.43 g of o-phenylenediamine and 0.6 g of tartaric acid (molar ratio = 1:2) were weighed and dispersed in a conical flask filled with 40 mL of ultrapure water. The precursor solution was prepared by ultrasonic dispersion for 20 minutes. The pH of the precursor solution was adjusted to 3.0 by adding 1 mol / L hydrochloric acid. The solid product was then heated in a microwave at a power of 1000 W for 1 minute. During purification, ultrapure water was added for ultrasonic dispersion, and the product was filtered three times through a 0.2 μm filter membrane to obtain a filtrate. The filtrate was then dialyzed for 24 hours using a dialysis bag with a molecular weight cutoff of 1500 Da. Finally, the dialyzate was freeze-dried to obtain carbon dot powder.

[0048] Example 3

[0049] The preparation method of carbon dots is as follows:

[0050] 0.86 g of o-phenylenediamine and 3 g of tartaric acid (molar ratio = 1:5) were weighed and dispersed in a conical flask filled with 200 mL of ultrapure water. The precursor solution was prepared by ultrasonic dispersion for 60 minutes. The pH of the precursor solution was adjusted to 5.0 by adding 1 mol / L hydrochloric acid, and then microwaved at a power of 50 W for 20 minutes to obtain a solid product. During purification, ultrapure water was added for ultrasonic dispersion, and the product was filtered three times through a 0.45 μm filter membrane to obtain a filtrate. The filtrate was then dialyzed for 24 hours using a dialysis bag with a molecular weight cutoff of 1000 Da. Finally, the dialyzate was freeze-dried to obtain carbon dot powder.

[0051] Example 4

[0052] The preparation method of carbon dots is as follows:

[0053] 3.5 g of o-phenylenediamine and 1.86 g of tartaric acid (molar ratio = 2:1) were weighed and dispersed in a conical flask filled with 100 mL of ultrapure water. The precursor solution was prepared by ultrasonic dispersion for 30 minutes. The pH of the precursor solution was adjusted to 1.0 by adding 1 mol / L nitric acid. The solid product was then heated in a microwave at a power of 600 W for 10 minutes. During purification, ultrapure water was added for ultrasonic dispersion, and the product was filtered three times through a 0.3 μm filter membrane to obtain a filtrate. The filtrate was then dialyzed for 24 hours using a dialysis bag with a molecular weight cutoff of 1000 Da. Finally, the dialyzate was freeze-dried to obtain carbon dot powder.

[0054] Example 5

[0055] The preparation method of carbon dots is as follows:

[0056] 0.86 g of o-phenylenediamine and 3 g of tartaric acid (molar ratio = 1:5) were weighed and dispersed in a conical flask filled with 80 mL of ultrapure water. The precursor solution was prepared by ultrasonic dispersion for 20 minutes. The pH of the precursor solution was adjusted to 3.0 by adding 1 mol / L sulfuric acid. The solid product was then heated in a microwave at a power of 100 W for 20 minutes. During purification, ultrapure water was added for ultrasonic dispersion, and the product was filtered three times through a 0.3 μm filter membrane to obtain a filtrate. The filtrate was then dialyzed for 24 hours using a dialysis bag with a molecular weight cutoff of 1500 Da. Finally, the dialyzate was freeze-dried to obtain carbon dot powder.

[0057] Example 6

[0058] A method for detecting copper ions using carbon dots, the specific steps are as follows:

[0059] (1) The carbon dots B-CDs prepared in Example 1 were added to a solution with a II-valent copper ion concentration of 1 to 100 nM (the concentrations were 1 nM, 5 nM, 10 nM, 15 nM, 20 nM, 30 nM, 40 nM, 50 nM, 60 nM, 70 nM, 80 nM, 90 nM, and 100 nM, respectively) to obtain dispersions with different II-valent copper ion concentrations, and the carbon dots were dispersed in the same volume of solution to obtain a blank carbon dot solution, wherein the concentration of the carbon dots in the solution was 50 μg / mL;

[0060] (2) Using a fluorescence spectrometer to measure the fluorescence intensity F1 of each dispersion and the fluorescence intensity F0 of the blank carbon dot solution; Figure 4 The emission spectra of the fluorescent carbon dots after adding different concentrations of II-valent copper ions in this embodiment. As the concentration of II-valent copper ions gradually increases, the fluorescence intensity of B-CDs gradually decreases;

[0061] (3) Fitting the fluorescence intensity F1, the fluorescence intensity F0 and the concentration of II-valent copper ions in the dispersion, Figure 5 The logarithm of the fluorescence intensity F1 after adding different concentrations of II-valent copper ions in this embodiment shows a linear relationship with the increase of II-valent copper ion concentration. The calibration curve is linear in the concentration range of 1 to 100 nM, and the linear fitting equation is Log 10 F1=-0.00921c+3.78588(nM,R 2 =0.99914), based on the triple signal-to-noise ratio (S / N=3) rule, the detection limit was 1.023 nM.

[0062] Example 7

[0063] A method for detecting copper ions using carbon dots, the specific steps are as follows:

[0064] (1) The carbon dots B-CDs prepared in Example 1 were added to a solution with a II-valent copper ion concentration of 1 to 100 nM (the concentrations were 1 nM, 5 nM, 10 nM, 15 nM, 20 nM, 30 nM, 40 nM, 50 nM, 60 nM, 70 nM, 80 nM, 90 nM, and 100 nM, respectively) to obtain dispersions with different II-valent copper ion concentrations, and the carbon dots were dispersed in the same volume of solution to obtain a blank carbon dot solution, wherein the concentration of the carbon dots in the solution was 20 μg / mL;

[0065] (2) Using a fluorescence spectrometer to measure the fluorescence intensity F1 of the dispersion and the fluorescence intensity F0 of the blank carbon dot solution; Figure 6 The emission spectra of the fluorescent carbon dots after adding different concentrations of II-valent copper ions in this embodiment. As the concentration of II-valent copper ions gradually increases, the fluorescence intensity of B-CDs gradually decreases;

[0066] (3) Fitting the fluorescence intensity F1, the fluorescence intensity F0 and the concentration of II-valent copper ions in the dispersion, Figure 7 The logarithm of the fluorescence intensity F1 after adding different concentrations of II-valent copper ions in this embodiment shows a linear relationship with the increase of II-valent copper ion concentration. The calibration curve is linear in the concentration range of 1 to 100 nM, and the linear fitting equation is Log 10 F1=-0.00947c+3.79722(nM,R 2 =0.99501), based on the triple signal-to-noise ratio (S / N=3) rule, the detection limit was 2.334 nM.

[0067] The concentration of carbon dots added to the copper ion solution is 1-100 μg / mL. Different fitting curve equations can be obtained as in Example 6 and Example 7. When used, the corresponding carbon dot concentration is selected for calculation.

[0068] Example 8

[0069] A method for recovering II-valent copper ions using carbon dots, the specific steps are as follows:

[0070] Adding carbon dot B-CDs to a 500 nM II-valent copper ion solution produced obvious flocculation. The carbon dot B-CDs were continuously added until the flocs no longer increased to obtain a suspension. The suspension was centrifuged at 10,000 r / min for 5 minutes to collect the flocculated precipitate, which was washed three times with ultrapure water. The flocculated precipitate was calcined at 700°C for 2 hours (in air atmosphere) to remove the carbon dots, and the copper ions were accurately recovered in the form of copper oxide.

[0071] Figure 8 This is a photo of flocculation precipitation taken in this example. When the amount of II-valent copper ions added is high, the generation of floccules can be observed with the naked eye.

[0072] Fig. 9 The SEM and element distribution diagram of the flocculation precipitate in this example show that the C, N, O, and Cu elements are evenly distributed.

[0073] Fig.10 The SEM and element distribution diagram of the product obtained by flocculation precipitation calcination in this example. The morphology of the calcined sample is a block structure, and the EDS spectrum shows that only Cu and O elements exist.

[0074] Fig.11 is the XRD diagram of the calcined sample in this example, showing that the phase after calcination is CuO, and there is no other impurity phase. The carbon dots have been completely removed after calcination, and the obtained product is pure CuO.

[0075] Example 9

[0076] A method for recovering II-valent copper ions using carbon dots, the specific steps are as follows:

[0077] Adding carbon dot B-CDs to a 300 nM II-valent copper ion solution produced obvious flocculation. Carbon dot B-CDs were continuously added until the flocs no longer increased to obtain a suspension. The suspension was centrifuged at 5000 r / min for 10 minutes to collect the flocculated precipitate, which was washed three times with ultrapure water. The flocculated precipitate was calcined at 800°C for 2 hours (in air atmosphere) to remove the carbon dots, and the copper ions were accurately recovered in the form of copper oxide.

[0078] Example 10

[0079] A method for recovering II-valent copper ions using carbon dots, the specific steps are as follows:

[0080] Adding carbon dot B-CDs to 400 nM II-valent copper ion solution produced obvious flocculation. Carbon dot B-CDs were continuously added until the flocs no longer increased to obtain a suspension. The suspension was centrifuged at 8000 r / min for 7 minutes to collect the flocculated precipitate, which was washed three times with ultrapure water. The flocculated precipitate was calcined at 900°C for 1 hour (in air atmosphere) to remove the carbon dots, and the copper ions were accurately recovered in the form of copper oxide.

[0081] According to the method of Example 6, carbon dots and copper ions at a concentration of 50 μg / mL were added to the actual water sample, and the fluorescence intensity of the water sample was detected. The concentration of II-valent copper ions was obtained in combination with the fitting curve obtained in Example 6, and the copper ions were recovered by the method of Example 8. The results are shown in Table 1. It is found that the detected concentration of II-valent copper ions is not much different from the actual addition amount, and the relative standard deviation does not exceed 8%. The recovery rate of copper ions is between 95.2% and 99.7%, indicating that the method of the present invention has good accuracy and can be applied to actual production.

[0082] Table 1

[0083]

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for detecting copper ions using carbon dots, characterized in that: The specific steps are as follows: (1) adding carbon dots to solutions containing different concentrations of II-valent copper ions to obtain dispersions of different concentrations of II-valent copper ions, dispersing the carbon dots into the same volume of water to obtain blank carbon dot solutions, wherein the concentrations of the carbon dots in the two solutions are 1 to 100 μg / mL; (2) Using a fluorescence spectrometer to measure the fluorescence intensity F1 of each dispersion and the fluorescence intensity F0 of the blank carbon dot solution; (3) Fit the fluorescence intensity F1, the fluorescence intensity F0 and the concentration of II-valent copper ions in the dispersion to obtain the logarithm of the fluorescence intensity F1 10 The linear relationship curve between F1 and II-valent copper ion concentration was obtained to obtain a linear fitting equation. The II-valent copper ion concentration in the solution was calculated according to the fluorescence intensity of the solution, and the copper ions in the solution were quantitatively detected.

2. The method for detecting copper ions using carbon dots according to claim 1, characterized in that: The preparation method of step (1) carbon dots is as follows: dissolving an organic amine and an organic acid in pure water, ultrasonically dispersing to prepare a precursor solution, adding an inorganic acid to adjust the pH value of the precursor solution to 1-7, heating the solution with a microwave until a solid product is obtained, adding ultrapure water to the solid product for ultrasonic dispersion, filtering with a microporous filter membrane to obtain a filtrate, dialyzing the filtrate, and freeze-drying the dialyzed solution to obtain carbon dot powder.

3. The method for detecting copper ions using carbon dots according to claim 2, characterized in that: The organic amines are fatty amines, alcohol amines, amides, alicyclic amines, and aromatic amines; the organic acids are aliphatic organic acids, aromatic organic acids, and terpene organic acids; the molar ratio of the organic amines to the organic acids is 1:5 to 5:1; and the volume of pure water is 5 to 100 times the total volume of the organic amines and the organic acids.

4. The method for detecting copper ions using carbon dots according to claim 2, characterized in that: The inorganic acid is hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid; the microwave power is 50-1000W, and the microwave heating time is 0.5-20min.

5. The method for detecting copper ions using carbon dots according to claim 2, characterized in that: The pore size of the microporous filter membrane is 0.10-0.45 μm; the molecular weight cutoff of the dialysis bag is 500-1500 Da.

6. A method for recovering copper ions using carbon dots, characterized in that: The specific steps are as follows: (a) adding carbon dots to a II-valent copper ion solution until no flocculation occurs, thereby obtaining a suspension; (b) centrifuging the suspension, collecting the flocculated precipitate, washing the flocculated precipitate with ultrapure water, and then drying; (c) The dried product is calcined in air to obtain a copper oxide product.

7. The method for recovering copper ions using carbon dots according to claim 6, characterized in that: In step (b), the centrifugal speed is 5000-10000 r / min, and the centrifugal time is 5-10 min.

8. The method for recovering copper ions using carbon dots according to claim 6, characterized in that: In step (c), the calcination temperature is 500-1000° C., the calcination time is 0.5-3.0 h, and the calcination atmosphere is air.

Citation Information

Patent Citations

  • Preparation method of carbon quantum dot fluorescent material and application of carbon quantum dot fluorescent material in copper ion detection

    CN109097032A

  • Method for recycling waste lithium ion battery anode material

    CN110563046A

  • Nanoparticle-carbon dot coated silicon dioxide composite nanoparticle with long-afterglow luminescence, long-afterglow material and preparation method

    CN113480995A

  • Dual-emission nitrogen-doped fluorescent carbon dots, preparation method and application thereof

    CN113831918A

  • Ethylenediamine-doped fluorescent carbon dots, preparation method thereof and application of ethylenediamine-doped fluorescent carbon dots in detection of copper ions in water body

    CN116606648A

Cited By

  • Synthesis of nitrogen-sulfur-carbon dots and preparation of pH-regulated Hg (II) / Cr (VI) / Mn (VI) sensing array

    CN120383934A

  • Multifunctional magnetic graphene quantum dot sensor, preparation method thereof and application of multifunctional magnetic graphene quantum dot sensor in detection of Cu < 2 + > in wastewater

    CN120609794A